Discovery of Selective Ligands for the Modulation of NMDA Receptors - Peltomaa,Klara (2025)
NMDA receptors are part of the family iGluRs that regulate the flow of positive ions, such as Na+, K+ and Ca2+, by ligand gating. Upon activation with Glutamate, the channel opens, and a flowthrough of ions occurs. NMDA receptors are unique in that they require the co-agonist glycine for activation and that they exhibit voltage-dependent ion flow due to Mg2+ blockade. The NMDA receptors have three subtypes, GluN1, GluN2 and GluN3 which in turn have subunits of their own. The NMDA receptors are constructed with two GluN1 subunits together with two GluN2 and/or GluN3 subunits. The GluN1/2 receptors are more important from a physiological perspective; thus, these receptors are the focus of this thesis, specifically GluN1/2A and GluN1/2B. The NMDA receptors are known for their role in excitotoxicity, which make them important targets for potential drugs against e.g. Parkinson’s disease and Huntignson’s disease. It has been proven difficult in making potent drugs for the NMDA receptors due to the high risk of side effects. The reason for this is that the different subtypes of the NMDA receptors are similar in structure but also that they are widely spread across the brain, thus targeting only one receptor is challenging. TCN213 is a scaffold that is selective for the GluN1/2A receptor with sufficient potency, binding at the interface, and able to cross the blood brain barrier. However, research on improving its potency and metabolism is ongoing. Different amide bioisostere analogues of the TCN213 scaffold have been synthesized to explore the amide part of this scaffold and study its importance in TCN213s activity. Important information of non-conserved amino acids between the subtypes GluN1/2A and GluN1/2B, specifically a switch from valine 267 to phenylalanine 262 respectively, have highlighted the theory behind the synthesis of the GluN1/2B analogues. Different synthetic approaches have been used to synthesize potential NAMs for the GluN1/2A and GluN1/2B receptors. However, their activity is yet to be determined.
Keywords: Organic chemistry; NMDA receptors; Potential drugs